2006
DOI: 10.1093/pcp/pcj100
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Survey of CK2 α and β Subunits in Arabidopsis: Multiple Isoforms Exhibit Differential Subcellular Localization

Abstract: Casein kinase 2 (CK2) is a ubiquitous enzyme essential for the viability of eukaryotic cells. In the present work we analyzed the Arabidopsis thaliana genome in a search for the genes coding for all CK2 alpha and beta subunits. We found four alpha subunit and four beta subunit genes. Expression analysis showed that all CK2 subunit genes are expressed in inflorescences, stems, leaves and roots. The level of expression of these genes is very similar, except for the one that codes for an alpha subunit harboring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 65 publications
6
112
0
Order By: Relevance
“…To test this hypothesis, we examined the subcellular localization of CK2a3 and CK2b3. A z-stack image of confocal sections showed that both subunits localized in the ER (Supplemental Figure 1) as well as in the nucleus, which is consistent with a previously reported site of CK2 localization (Salinas et al, 2006).…”
Section: Ck2a3/b3-mediated Phosphorylation Of Pts Under Pi-sufficientsupporting
confidence: 90%
See 1 more Smart Citation
“…To test this hypothesis, we examined the subcellular localization of CK2a3 and CK2b3. A z-stack image of confocal sections showed that both subunits localized in the ER (Supplemental Figure 1) as well as in the nucleus, which is consistent with a previously reported site of CK2 localization (Salinas et al, 2006).…”
Section: Ck2a3/b3-mediated Phosphorylation Of Pts Under Pi-sufficientsupporting
confidence: 90%
“…The human genome has two genes encoding catalytic a-or a9-subunits and only one for the regulatory b-subunit (Wirkner et al, 1998;Ackermann et al, 2005), whereas plant genomes frequently have multigene families that encode each subunit (Espunya et al, 2005;Salinas et al, 2006). For example, four and two genes in rice encode CK2a and CK2b, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively weak phosphorylation by the catalytic ␣ subunit and strong stimulation by the regulatory ␤ subunit might provide plants with enhanced regulatory power to modulate PIF1 activity in vivo. Moreover, CK2 subunit genes are differentially expressed in different tissues (39), suggesting that PIF1 might also be regulated in a tissue-specific manner.…”
Section: Pif1 Ismentioning
confidence: 99%
“…The CK2 holoenzyme consists of two catalytic ␣ and two regulatory ␤ subunits. The Arabidopsis genome has four ␣ subunit and four ␤ subunit genes (39). Various members of both the ␣ and ␤ subunit families have been shown to be localized in the cytoplasm, nucleus, and also in chloroplasts (39).…”
mentioning
confidence: 99%
See 1 more Smart Citation